The Dimension of Human Nature in Novel Totto-chan: The Little Girl in the Window - Cahya Ningsih, Ade (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Basically, every child is born with a good character. They are a mandate from God who is blessed with extraordinary potential. This is what is then called human nature. Human nature believes that every child has the potential or uniqueness of each that deserves to be developed. A good educational institution should organize learning based on human nature because every child is born with a nature. One example of providing education based on human nature is the education in Tomoe Gakuen in the novel Totto-chan: The Little Girl in the Window by Tetsuko Kuroyanagi. In this study, the author tries to describe the dimensions of human nature implied in the novel. The research method used is literature study because it uses novel book media as the main object of research. The data was collected using a documentation technique, where the author reads the contents of the novel as a primary data source as a whole and records data relevant to the object of research. The author also reads and records data obtained from books or other similar studies as secondary data sources so that detailed data results are obtained. The data analysis technique in this study uses Paul Ricoeur's hermeneutic theory and has three main steps, namely the symbolic step, the step of giving meaning to the symbol, and the step of philosophical thinking. The results of this study indicate that the dimensions of human nature in the novel are reflected in humanist education, flexible and independent learning, and focus on children's potential.